Cubic Root Mean Difference Labeling Of Graphs - Tanveera Sultana. H.M, V.J.Sudhakar (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Graceful and Harmonious Labeling, variation of graceful labeling are studied by Gallian [1]. The concepts of labeling by Somasundaram and ponraj[5]. Root square mean labeling of graphs has been introduced by sandhya , somosundaram and Anusa[8]. By the motivation of above works we introduce a new type of Labeling called cubic root Mean Labeling of graphs